2017
DOI: 10.1016/j.jtcme.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Understanding nutrition and immunity in disease management

Abstract: As we search for answers to modern medicine's most prevalent and challenging problems, the relationship between nutrition, immunity, and biological function of various natural compounds are preimminent. Nutritional research involving genomics provides rational capabilities for preventing disease. Scientific advances in genomic sequencing reveal opportunities for exploring diet-health relationships and potential for individual, genotype based dietary recommendations. Utilizing molecular and genetic technology t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…Several epidemiological studies have shown that nutrition has critical roles in the preservation of health and the pathogenesis and treatment of diseases. In diseases, there is an association between nutrition and immunity that, from an evolutionary point of view, has shown a close connection in the development and function of the immune system (Cooper & Ma, 2017). Phagocytosis is the most primordial and universal modality of food procurement and defense against foreign agents in unicellular invertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies have shown that nutrition has critical roles in the preservation of health and the pathogenesis and treatment of diseases. In diseases, there is an association between nutrition and immunity that, from an evolutionary point of view, has shown a close connection in the development and function of the immune system (Cooper & Ma, 2017). Phagocytosis is the most primordial and universal modality of food procurement and defense against foreign agents in unicellular invertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the index of economic well-being could be explained by the fact that a population often living in poverty is prone to a difficulty of social life in general including undernourishment that would expose it to malnutrition. Among the consequences of malnutrition, we have a decrease of immunity and therefore susceptibility to catch infections including bacteria [ 15 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is ample evidence to show that impaired immunity is a critical adjunct factor in malnutrition-related infection. 8,9 This applies not only to young children in developing countries but to all age-groups in all subsets of population like elderly and those with eating disorders and primary debilitating diseases. 10,11 However, the chance for reversibility is a ray of hope.…”
Section: Nutrition a N D Immunitymentioning
confidence: 99%